Design District Gran Concepción: Territory development through design driven innovation - Alarcón, Jimena (Base Diseño e Innovación, 2018)
This initiative aims to promote a design district for the greater Concepción, making visible a network of territorial value that evidences the offer of products and design services, favoring associativity, and positioning the region as a competitive nucleus with international projection. This is how, in spring 2016, we attended the foundation of the first design district in Chile and, with it, fifty six companies conceived from an active design philosophy gained visibility. The ultimate goal is to inform and motivate tourists and locals to admire, enjoy and purchase local design. Likewise, companies are certified with the design district quality seal, which provides support for unique creativity concepts. Design allows companies to differentiate from their competitors, optimize the communication of their values, and make products that are adapted to the needs of users that are more respectful with the environment. This generates environments leading to a better quality of life as well as synergies that enhance development articulated with a harmonious territory. A greater design culture implies strengthening the local creative industries and highlighting their contribution to the business ecosystem.